Implementasi Metode Hybrid PID-Fuzzy Control untuk Kontrol Hovering pada Pesawat UAV Quadcopter - Imam Suhendra; Andik Yulianto (Telcomatics, 2017)
Quadcopter is an unmanned aerial vehicle with 4 rotors and propellers on each side. All motions, positions and flying directions are controlled by the speed and direction of each rotor movement. Application of this quadcopter technology also varied, such as for distant aerial observation and militer duties. In the application of this technology, the balance of quadcopter is needed, four rotors will always be parallel to the horizontal plane. This condition is known as hovering control. Hovering control often got distractions from outside, among others is the dynamics of the plant tend to be complex. In this study used methods of Hybrid PID-Fuzzy control as its control system to achieve a balanced condition and resolve any distractions when hovering control happen for roll and pitch angles. Hybrid PID-Fuzzy control is combination method of PID control (conventional PID) with output value generated from fuzzy logic control. Constants of Kp, Ki and Kd are used and added with fuzzy logic control using 25 rule evaluations. Percentage of each control is 90% for PID control and 10% for fuzzy logic control. With constant Kp=6.62, Ki=0.85, Kd=5 with 25 rule evaluations, this control can generate good response by reducing overshoot and provide better recovery time compared with conventional PID control. Implementation of Fuzzy-PID hybrid control generates an error steady state response about 3o during hovering and being able to hovering back within 1.5 seconds if the given disctraction is 19o and 1 second if the given distraction of 13 o.